In The Name Of God Theory of Separation of Powers and Organization of Political Power of State - Seyed Mohammad Tabatabaei (دولت‌پژوهی, 2018)
Following the national revolutions which caused the creation of a new formation of state known as nation-state, we have witnessed the practical implementation of Theories of Separation of Powers. Ever since, the functional principles of organizing power in the modern state were based on the new theories about the separation of powers and their different perceptions. As a matter of fact, in order to prevent the centralization of power and to build a better organization of political affairs on the basis of Theory of Separation of Powers, the nation-states tried to the divide political power into three branches: the executive, the legislative and the judicial powers and separate them on the basis of their structures and functions. The present paper will attempt to identify the cause and the extent of remoteness or closeness of the ternary shapes of the combination of powers, relative or complete separation of powers of the known principles of democracy. The basic argument of the present research is based on the point that the true and complete implementation of the principle of “check and balance” among the ternary branches has caused more limitation on the power and constructive interactions; as a result, in a lenient system of the contribution of powers we witness the creation of a kind of “power equation” and “democratic balance” through the relative separation of powers.